Một mô hình để biểu diễn hành vi và phân tích các hệ thống phân tán - Hưng, Đặng Văn (Journal of Computer Science and Cybernetics, 2016)
The present paper gives a formal model for analyzing distributed systems and representing their behavior. The model is proved to be simple and powerful enough in studying the problems concerning distributed systems. Some synchronization techniques are considered, and an algorithm for determining states of distributed systems is given.